Neutrophil Extracellular Traps Effectively Control Acute Chikungunya Virus Infection - Hiroki, Carlos H.; Toller-Kawahisa, Juliana E.; Fumagalli, Marcilio J.; Colon, David F.; Figueiredo, Luiz T. M.; Fonseca, Bendito A. L. D.; Franca, Rafael F. O.; Cunha, Fernando Q. (Frontiers in Immunology, 2020)
Chikungunya virus (CHIKV) is a re-emerging arbovirus, in which infection causes a febrile illness also commonly associated with severe joint pain and myalgia. Although the immune response to CHIKV has been studied, a better understanding of virus-host interaction mechanisms may lead to more effective therapeutic interventions. In this context, neutrophil extracellular traps (NETs) have been described as a key mediator involved in the control of many pathogens, including several bacteria and viruses, but no reports of this important protective mechanism were documented during CHIKV infection. Here, we demonstrate that experimental infection of mouse isolated neutrophils with CHIKV resulted in NETosis (NETs release) through a mechanism dependent on TLR7 activation and reactive oxygen species (ROS) generation. In vitro, mouse isolated neutrophils stimulated with PMA (phorbol 12-myristate 13-acetate) release NETs that once incubated with CHIKV, result in further virus capture and neutralization. In vivo, NETs inhibition by treatment of the mice with DNase resulted in enhanced susceptibility of IFNAR-/- mice to CHIKV experimental acute infection. Last, by accessing the levels of MPO-DNA complex on acutely CHIKV-infected patients, we found a correlation between the levels of NETs and viral load in the blood, suggesting that NETs are also released in natural human infection cases. Altogether, our findings characterize NETosis as a contributing natural process to control CHIKV acute infection, presenting an antiviral effect that helps to control systemic virus levels.